Chicken egg-white extracts promote OCT4 and NANOG expression and telomeres growth in 293T cells - Ruan, G-P.; Yao, X.; Shu, J.; Liu, J-F.; Pang, R.-Q; Pan, X-H. (Cellular and Molecular Biology, 2017)
It will have broad applications in cell biology if one of egg cell extracts has the roles to promote cell proliferation and reprogramming. It will provide a new method for easier reprogramming somatic cells and promote cell proliferation. We found chicken egg-white extracts have roles to promote cell proliferation and reprogramming. The different ingredients were then assessed for cell proliferation activity and somatic cell reprogramming. Chicken egg-white extract ingredients that were less than 3 kDa (LT3K) promoted cell proliferation. Those ingredients that were greater than 3 kDa (GT3K) promoted the increased expression of pluripotency factors in somatic cells and promote telomeres growth in 293T cells. Chicken egg-whites can be separated into ingredients of LT3K, which act to promote cell proliferation, and GT3K, which can be used to promote somatic cell reprogramming.